Self-Care Activities among Old Age with Diabetic Foot Ulcer in Iraq - Ahmed Mohammed Jasim Shlash; Ridha M. Lefta; Shady Shafeek Dowarah; Karim Jabur Diadan (Medical Journal of Babylon, 2025)
Background: Diabetic foot ulcer patients have different self-care activities, yet many of them do not know their importance in reducing symptoms and progression of the disease and preventing access to amputation of the foot. Objective: To identify self-care activities among old age with diabetic foot ulcer patients and identify the socio-demographical characteristics and clinical data of the study sample. Find out the relationship between the socio-demographical characteristics and clinical data with the patient’s self-care activities. Materials and Methods: Descriptive cross-sectional study design. The study relied on the interview methods of a total of 100 patients. A non-probability convenience sample was used to select study sample. The study was conducted from 10th October 2021 to 15th May 2022 in Karbala city. Results: The study results show the highest percentage of the study samples were between 63 and 72 years old, educational attainment (25%) postgraduate, most of the study sample urban in percentage (66%), retired in percentage (31%), males in percentage (64%), and married in percentage (75%). Most of them (54%) have sufficient income to some extent. Concerning type of diabetes treatment, more percentage of the study samples used both insulin and oral hypoglycemic agents in percentage (47%), most of them have one another comorbidities besides diabetic foot in percentage (35%), the self-care activities of patients were within fair level by mean of score is (1.87%) in percentage (80%). Conclusions: Diabetic foot patients’ adherence to self-care activities was unsatisfactory. This may be due to a lack of education and correct practices about foot care. The patient must assume responsibility for themselves in the first place, as well as hospitals take a greater responsibility to inspire the self-care activities in caring for themselves.